Psychosociology of Addiction and Rehabilitation: Construction of a Psychometric Instrument for screening problem and pathological gambling - Charonitaki, Aikaterini; Zhuravliova, Irina; Koskinas, Konstantinos (Homo Virtualis, 2020)
Gambling and gambling disorders have received solicitous attention by clinicians and researchers during the past three decades. The majority of existing psychometric instruments relevant to problem gambling are based on the clinical evaluation of symptomatology. The aim of this study was the development and evaluation of a self report instrument that comprehends elements based on three main factors: a. psychological, b. biological, c. sociological. In the first phase of this research, structured and semi-structured interview was conducted in 16 individuals. In the second phase, a pilot inventory that consisted of 227 items, was administered in 91 individuals of general population. In the last phase of this study participated 200 individuals from the community and completed the short form of the inventory that included 148 items. Factor analysis was conducted in all items and 115 statistically significant questions were derived which comprise the final form. The present instrument, which has demonstrated satisfactory psychometric properties, provides a first step in self evaluation of problem and pathological gambling in Greece and aims at effective counseling in order to reduce or even prevent addictive gambling behaviors.